Model for the Development of Independent Cognitive Activity in Primary School Students through Self-Assessment - Alisherovna, Makhmudova Nodira (Research Parks Publishers, 2023)
this article provides an idea of the importance of independent work or creative assignments in educational activities in order to improve the model of development of independent cognitive activity in students through self-assessment, modeling, the process of self-assessment, as well as in the methods of self-assessment.